Technical diagnostics of objects using active imaging - Marek Piszczek (Biuletyn Wojskowej Akademii Technicznej, 2015)
The article presents an original method of the space-time framing as a potential tool for technical diagnostics. Because of the unusual observation and measurement properties such as the selection of the observed spatial scenes, the proposed technique of recording video data can be used in many situations where traditional cameras are not able to assume the tasks. The proposed use of the experimental Laser Photography Device (LPD) concerns the issue of diagnosis of steam turbine blades.[b]Keywords[/b]: active imaging, image processing, diagnostics